University student̕ s entrepreneurial journey obstacles in Costa Rica - Aguirre-González, Juan Antonio (2020)
This study sought to identify the obstacles that limit the entrepreneurial desire among university students, in order to provide accurate guidance to universities, as well as to encourage university students’ entrepreneurial behaviour. The final sample includes information from 1458 university students (Costa Rican private university). Cronbach alpha estimates were employed in the empirical analysis. Additionally, a descriptive sociodemographic analysis based on ordinal logistic regression models was used to identify variables associated to each of the stages of the process. The findings indicate that the most influential factors explaining the entrepreneurial intention of university students are the lack of innovative ideas, the perception about business people, their age, their management background, the government support, the education level of the mother, the father’s economic activity, and the awareness of what it means to own and run a business.